2023
DOI: 10.1021/acsami.3c02671
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Cyano Functionalized Benzo[d]imidazol-2-ylidene Ir(III) Phosphors for Blue Organic Light-Emitting Diodes

Abstract: In this study, we designed and synthesized three series of blue emitting homoleptic iridium(III) phosphors bearing 4(5-mfcp) cyclometalates, respectively. These iridium complexes exhibit intense phosphorescence in the high energy region of 435−513 nm in the solution state at RT, to which the relatively large T 1 → S 0 transition dipole moment is beneficial for serving as a pure emitter and an energy donor to the multiresonance thermally activated delayed fluorescence (MR-TADF) terminal emitters via Forster res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Their pincer carbene chelate E possesses a planar configuration from which the peripheral carbene chelates exhibit slightly longer Ir–C­(carbene) bond distances (i.e., 2.054(5)–2.060(5) Å) in comparison to those of the central Ir–C­(aryl) distance (1.964(4)–1.965(4) Å). The variation of these Ir–C distances are different from those observed in the tris-bidentate Ir­(III)-based carbene complexes to which the Ir–C­(carbene) distances are always shorter than the respective Ir–C­(aryl) distance. On the other hand, these bonding patterns are consistent with the bis-tridentate Ir­(III) complexes bearing the analogous carbene pincer chelate . Hence, we concluded that the shortened Ir–C­(aryl) distances of carbene pincer chelate were caused by the geometrical constraint imposed by the peripheral carbene entities .…”
Section: Resultsmentioning
confidence: 57%
“…Their pincer carbene chelate E possesses a planar configuration from which the peripheral carbene chelates exhibit slightly longer Ir–C­(carbene) bond distances (i.e., 2.054(5)–2.060(5) Å) in comparison to those of the central Ir–C­(aryl) distance (1.964(4)–1.965(4) Å). The variation of these Ir–C distances are different from those observed in the tris-bidentate Ir­(III)-based carbene complexes to which the Ir–C­(carbene) distances are always shorter than the respective Ir–C­(aryl) distance. On the other hand, these bonding patterns are consistent with the bis-tridentate Ir­(III) complexes bearing the analogous carbene pincer chelate . Hence, we concluded that the shortened Ir–C­(aryl) distances of carbene pincer chelate were caused by the geometrical constraint imposed by the peripheral carbene entities .…”
Section: Resultsmentioning
confidence: 57%
“…Hence, these hyper-OLEDs also exhibited lower turn-on voltages and higher maximum EQE and EQE at a brightness of 1000 cd m −2 in comparison to the pure MR-TADF devices recorded using ν -DABNA under identical device architecture. 69 Furthermore, the EL spectrum also exhibited a large reduction in FWHM from 58 nm for the parent device to 19 nm and 29 nm for terminal emitters ν -DABNA and t -DABNA, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…5a. 69 The hole-transport layer (HTL) and electron-transport layer (ETL) consisted of mCP and 3TPYMB, respectively. Thin layers of 4 wt% ReO 3 doped mCP and Liq were also applied to enhance the carrier and charge injection from the respective electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, MR-TADF terminal emitters are the preferred choice for giving narrowband blue emission. 41 With this in mind, we examined hyper-OLEDs by incorporating f -ct4a , f -ct4b , and f -ct4c as sensitizers along with 1–2 wt% of DtBuCzB 42 as a blue terminal emitter (Fig. 6 and Table 4).…”
Section: Resultsmentioning
confidence: 99%